The physics and mathematics of javelin throwing - Hatton, L. (2005)
Javelin flight is strictly governed by the laws of aerodynamics but there remain well-entrenched but misleading views about the factors involved. This paper gives a simplified but accurate view of the physics and dynamics of javelin flight and describes a software implementation of these.